Handbook on Antimicrobial Resistance Current Status, Trends in Detection and Mitigation Measures - Mothadaka, Mukteswar Prasad; Vaiyapuri, Murugadas; Rao Badireddy, Madhusudana; Nagarajrao Ravishankar, Chandragiri; Bhatia, Rajesh; Jena, Joykrushna (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Antimicrobial resistance (AMR) is a global public health threat. The menace of antimicrobial resistance is present across health, animal, agriculture, food, and environment sectors. It, therefore, requires an inter-disciplinary combat approach- the one health approach, envisaged by the FAO-UNEP-WHO-WOAH Quadripartite (Food and Agriculture Organization of the United Nations (FAO), the UN Environment Programme (UNEP), the World Health Organization (WHO) and the World Organisation for Animal Health (WOAH). This comprehensive reference book provides a thorough understanding of antimicrobial resistance across different sectors. It presents deep insights and gives a global perspective on antimicrobial resistance for policymakers. The book offers essential and up-to-date information that enables researchers from multiple fields to design research on antimicrobial resistance. The book discusses molecular mechanisms and antibiotic resistance genesof significant antimicrobial-resistant pathogens, regulatory frameworks available worldwide, and mitigation strategies across the sectors, including probiotics, prebiotics, antimicrobial peptides, bacteriophages, phytochemical compounds, immunostimulants, vaccines, bacteriocins, etc. It compiles essays from leading experts in the field of antimicrobial resistance research. The book is meant for students and researchers in microbiology, medical microbiology, and public health. It is also helpful for clinicians and policymakers. .
Default -- Status of AMR across Sectors -- Antimicrobial Usage -- Insights on Antimicrobial resistance in pathogens -- Drivers of AMR and recent trends in detection and characterization of AMR pathogens -- Mitigation measures across the sectors -- .
Keywords: Immune response; Pathogenic microorganisms; Microbiology; Bacteria; Medical microbiology; Antimicrobial Responses; Microbiology; Bacteria; Medical Microbiology